Analysis of deafness gene screening results in 15771 newborn cases in Anyang city of Henan - Mu, Yanchao; Han, Meiqing; Li, Yang; Di, Hua; Li, Zhengxin; Li, Haiyan; Wang, Dawei; Li, Xue; Zhang, Lei; An, Huiping (Frontiers in Pediatrics, 2025)
ObjectiveTo analyze the prevalence and mutation spectrum of deafness-associated genes among newborns in Anyang City.MethodsHeel blood samples were collected from 15,771 newborns. Thirteen mutation sites across four genes associated with hereditary deafness (GJB2, SLC26A4, GJB3, and 12S rRNA) were detected using PCR combined with a flow-through hybridization technique.ResultsA total of 605 newborns were identified as carriers of pathogenic variants, yielding an overall carrier rate of 3.836%. Specifically, 254 newborns carried GJB2 gene variants (carrier rate: 1.611%), including one homozygous variant. Heterozygous variants in the SLC26A4 gene were found in 257 newborns (carrier rate: 1.630%). Heterozygous GJB3 variants were detected in 49 newborns (carrier rate: 0.311%). Homoplasmic or heteroplasmic variants in the 12S rRNA gene were present in 42 newborns (carrier rate: 0.266%). Additionally, ten newborns carried heterozygous variants in two different genes concurrently. Five 12S rRNA variants found in this study were not documented in public databases. The frequency of deafness gene variants in descending order was SLC26A4, GJB2, GJB3, and 12S rRNA. The most common pathogenic variants identified were GJB2 c.235delC and c.299_300delAT, and SLC26A4 c.919-2A > G and c.2168A > G, consistent with findings from other regions in China.ConclusionImplementing newborn genetic screening for deafness in this region facilitates the early identification of individuals at risk for congenital, delayed-onset, and aminoglycoside-induced hearing loss, enabling timely intervention and follow-up.